PENERAPAN MODEL PEMBELAJARAN POE UNTUK MENINGKATKAN KETERCAPAIAN KOMPETENSI DASAR SISWA - Atriyanti, Yuli; Hadisaputro, Subiyanto (Chemistry in Education, 2015)
This research aimed to determine of the implementation of learning model of POE (Predict, Observe, Explain) can improve studentâs achievement of basic competencies the hydrolysis of the salt material. The population in this research was students of XI IPA SMAN 1 Tengaran in academic year 2013/2014. In selecting the sample, the researcher used cluster random sampling technique because the populationâs distribution was normal and homogeneous. Design used in this research is pretest-posttest group design. Data collection in this research was using test, observation, questionnaire and documentation. The result of data analysis indicated the implementation of POEs learning model can improve students achievement of basic competencies of the material salt hydrolysis. The test results of N-gain for the experiment class is 0.24 and 0.16 for the control class. This means there is an increased of students achievement. To determine which one better of both group then the test average difference one side (right side) was done. The test result showed the value of t-test of 2.00 while t-critical 0.063 so that it can be concluded that achievement the basic competencies of students in experimental class is better than control class.